LEVANTAMENTO DA ICTIOFAUNA DE RIACHOS DE CABECEIRA DA BACIA DO RIO MIRANDA, ALTO RIO PARAGUAI, MATO GROSSO DO SUL, BRASIL - FERREIRA, Fabiane Silva; DUARTE, Gabriela Serra do Vale; SEVERO-NETO, Francisco; Froehlich, Otávio; SÚAREZ, Yzel Rondon; VICENTIN, Wagner (ANAIS DO ENIC, 2017)
-